MOTORCYCLE-PROPELLED PUBLIC TRANSPORT AND LOCAL POLICY DEVELOPMENT - Marie Danielle V. GUILLEN (IATSS Research, 2004)
In most developing countries, motorcycles are part of the essential mode of transportation. In the case of the Philippines, local public transport in the form of tricycles as well as “habal-habal”, or “motorcycle taxi” exists. This paper reviewed the local transport policy development with regards to innovating motorcycles as tricycles or using motorcycles as a public transport mode. It assumes that motorcycle-propelled public transport precedes the development of local public transport policy. Davao City is chosen as the site for the case study since a wide variation of motorcycle-innovations can be observed. Philippine tricycle is classified as a motor vehicle composed of motorcycle fitted with a single wheel sidecar or with a two-wheel cab, operated as a public transport for a fee. In Davao City, three forms of tricycles can be observed: side-cab, center-cab and open cab. An emerging mode, in the form of motorcycle taxi known as “habal-habal” can also be found. The study shows that the presence of various motorcycle-propelled public transport in Davao City is attributed to inadequacy of either national or local policy that defines its operation and physical design. The policy response of eliminating “triciboat” and the presence of private motorcycle credit facility led to the emergence of informal and illegal modes like the “habal-habal” and open-cab tricycles. The issues and gaps in policy implementation and the importance of relating policies to local urban and transportation planning and management were discussed.